POPULATION STRUCTURE AND HABITAT CHARACTERISTICS OF CLAM (Meretrix meretrix) IN THE INTERTIDAL ZONE OF TELUK LANCAR VILLAGE, BENGKALIS REGENCY - Ardiana, Eka; Zulkifli, Zulkifli; Efriyeldi, Efriyeldi (Asian Journal of Aquatic Sciences, 2025)
Clam (Meretrix meretrix) is an economically and ecologically significant bivalve mollusk. This study aimed to determine the population structure and habitat characteristics of M. meretrix in the intertidal zone of Teluk Lancar Village, Bengkalis Regency. The research employed a survey method from November 2024 to February 2025, focusing on one station divided into three subzones (Upper, Middle, Lower). Results revealed that the sediment substrate was predominantly sandy mud with organic matter content ranging from 0.5% (middle zone) to 2% (upper zone). The highest abundance of M. meretrix was found in the middle subzone (3.1 ind/m²), while the lowest was in the upper subzone (2.0 ind/m²). No significant differences in abundance were observed between stations or intertidal subzones. Size distribution analysis revealed that the 2.68-3.17 cm class was the most common (15 individuals), while the 1.18-1.67 cm and 4.16-4.67 cm classes were the least represented (1 individual each). The distribution pattern of M. meretrix was uniform (Id < 1).